The peasantry as a way of life: peasant production in the village Serrote Grande, Craíbas / AL / O campesinato como modo de vida: a produção camponesa no povoado Serrote Grande, Craíbas/AL - Lívia Thaysa Santos de Albuquerque Gama; Cirlene Jeane Santos e Santos (Universidade Estadual de Alagoas, 2017)
This article has as its central theme, "The Peasantry as a way of life: Analysis of peasant production in the Povoado Serrote Grande, Craíbas/AL". In this sense, it presents how the way of life of the peasants residing in the community and the relations of production are constructed. It presents the structural elements that mark the existence of the peasantry, as well as the discussion related to the subordination of this way of life to capital. The objectives are based on the analysis of how peasant production, the organization of geographic space and the production relations established in Serrote Grande village, taking into account the peasant way of life in the community. The research was carried out from the bibliographical survey on the proposed theme, technical exploratory field visit and the construction of an iconographic collection. Therefore, practical and theoretical procedures were used in order to obtain data for the basis of the research presented here.